Meta-Analysis of the Prognostic Impact of Stroke Volume, Gradient, and Ejection Fraction After Transcatheter Aortic Valve Implantation - Eleid, Mackram F.; Goel, Kashish; Murad, M. Hassan; Erwin, Patricia J.; Suri, Rakesh M.; Greason, Kevin L.; Nishimura, Rick A.; Rihal, Charanjit S.; Holmes, David R. (The American journal of cardiology, 2015)
The prognostic implications of several baseline preprocedural variables in patients with severe native valve aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI) are unclear. The goal of this study was to determine the impact of reduced stroke volume index (SVI), low gradient (LG), and reduced ejection fraction (EF) on all-cause mortality. We searched MEDLINE, CENTRAL, EMBASE, Web of Science, and Scopus through October 13, 2014. We evaluated the association between low SVI (<35 ml/m2), LG (<40 mm Hg), and low EF (<50% and <30%) on 1-year all-cause mortality. We pooled results across studies using the random-effects model. We included 16 studies at moderate risk of bias enrolling 7,673 patients with severe AS who underwent TAVI. Low EF was associated with increased 1-year mortality after TAVI compared to preserved EF (for EF <30%, hazard ratio [HR] 1.60, 95% confidence interval [CI] 1.19 to 2.16, I2 = 32%; and for EF <50%, HR 1.52, 95% CI 1.31 to 1.76, I2 = 17%). LG was associated with increased mortality after TAVI compared to high mean gradient (≥40 mm Hg; HR 1.60, 95% CI 1.30 to 1.97, I2 = 36%). Low SVI was associated with increased mortality after TAVI compared to normal SVI (HR 1.59, 95% CI 1.23 to 2.05, I2 = 27%). In conclusion, low SVI, LG, and low EF are each associated with higher mortality after TAVI. These findings highlight the importance of including these variables into TAVI risk algorithms and will better inform shared decision-making before TAVI.